Decentralized Capital, Centralized Growth? A Qualitative Synthesis on the Role of Venture Capital in Reinforcing Innovation Hubs - Mia Christy Patricia; Yuni Sara (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review explores the paradox of decentralized capital contributing to the continued centralization of innovation activity within established geographic hubs. Drawing on recent empirical studies, the review synthesizes findings on how venture capital (VC), though increasingly distributed across regions, remains concentrated in innovation ecosystems such as Silicon Valley, Boston, and New York. The analysis highlights factors including relational investing, agglomeration economies, and institutional embeddedness that reinforce this geographic concentration. While remote investing and public policy efforts aim to expand capital access, they often fall short of disrupting entrenched spatial dynamics. The findings underscore how venture capital acts not merely as a financial resource but as a structuring force that shapes the geography of innovation. The study contributes to understanding the limitations of capital diffusion in fostering regional entrepreneurial development and calls for more integrative policy interventions to balance growth.